The Influence of Occupational Stress, Anxiety, Work Engagement and Perceived Organizational Support on Innovation Outputs at XYZ Hospital During COVID-19 Pandemic - Audrina Ernes; Albert Surya Wanasida (Jurnal Manajemen Kesehatan Indonesia, 2023)
Innovative approaches are needed to improve health, prevent disease, implement new treatments and deliver safe, high-quality care,this has always been important, but during the current COVID-19 pandemic, it has become even more relevant. The purpose of this study is to examine the relationship between the antecedents of Innovative Behaviour and Innovation Outputs in nurses who work at XYZ Hospitals, incorporating Innovative Behaviour as a mediator. This study used a quantitative survey with a purposive sampling technique to collect data from nurses in XYZ hospital in Banten Province. There are 160 eligible respondents. The data were analyzed with PLS-SEM using SmartPLS software. It was found that Innovative Behaviour has a positive and significant influence on Innovation Outputs. Work Engagement, as well as Perceived Organizational Support, was found to have a positive and significant influence on Innovative Behaviour. Meanwhile, Occupational Stress and Anxiety didn’t have a significant influence on Innovative Behaviour. This study has implications for hospital management in developing nurses’ innovative behaviour and innovation outputs.